Monte Carlo simulation of water-tetrahydrofuran mixtures - Freitas, Luiz Carlos Gomide; Cordeiro, João Manuel Marques [UNESP] (Elsevier B.V., 1995)
Monte Carlo simulations of water-tetrahydrofuran (THF) mixtures were performed in the isothermal-isobaric ensemble (NPT) at T = 298 K and p = 1 atm. The interaction energy was calculated using the TIP4P model for water and a five-site united atom representation for the THF molecule. The potential energy surfaces for water-THF interactions were obtained by using combining rules and the original potential functions used for pure liquids. Theoretical values obtained for the average interaction energy as a function of concentration are in good agreement with available experimental data. Results from the partitioning of the total interaction energy into water-water, water-THF and THF-THF contributions are presented. These results are useful to distinguish between the quantitative contributions of these molecular interactions to the energetic behavior of the water-THF mixing process. The radial distribution functions for HW-OTHF and OW-OTHF site-site interactions show the salient features of hydrogen-bonded liquids. Comparison of the average number of water-water complexes interacting through hydrogen bonding in water-THF and water-methanol mixtures shows an enhancement of the water-water coordination number in a THF rich environment. © 1995.